Pemberdayaan UMKM Kota Semarang melalui Edukasi Pajak Berkelanjutan - Ika Pratiwi; Dian Kusuma Wardhani; Hetika Hetika; Fairuz Lerian Puspita Hapsari; Ari Yudiansyah (GOTAVA, 2025)
Taxation is one of the primary sources of state revenue vital to national development. However, tax compliance among MSME actors in Semarang City remains low due to limited literacy, information, and tax outreach. To address this challenge, the Vocational School of Diponegoro University, through the D4 Tax Accounting Study Program, in collaboration with Piranha Smart Center, implemented a community service program in the form of tax training targeting the public and MSME actors. The activity involved 120 participants divided into six batches, utilizing face-to-face training methods and the provision of learning modules. Evaluation results showed significant improvements in participants’ knowledge, understanding, awareness, and tax compliance, each achieving a success rate above 70%. This achievement was reflected in the positive responses from participants regarding the training materials and modules provided. The program has proven effective in enhancing community capacity to fulfill tax obligations independently and contributes to sustainable development.